Exploring Early Numeracy Development Through Concrete Manipulative Play: A Qualitative Study of 5–6 Year Old Children in an Indonesian Kindergarten - Nauratuddini, Nauratuddini; Christianti, Martha (THUFULA, 2026)
This study explores early numeracy development through concrete manipulative play among children aged 5–6 years in an Indonesian kindergarten. The study addresses the challenge of developing numeracy skills in early childhood, particularly when learning experiences rely heavily on abstract instruction rather than direct interaction with meaningful materials. A descriptive qualitative approach was employed at TK Pembina Bantul, involving 24 children and two teachers. Data were collected through participatory observation, semi-structured interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that concrete manipulative play supports children’s understanding of fundamental numeracy concepts through hands-on engagement with familiar objects from their immediate environment. Children demonstrated one-to-one correspondence by matching vegetable replicas to written numerals, arranging wooden blocks by size and dimension, classifying buttons by color, and applying comparison symbols to represent quantitative relationships. These activities enabled children to develop conceptual understanding of quantity, classification, seriation, and numerical symbols through meaningful and enjoyable learning experiences. The study highlights three factors that facilitated numeracy development: the use of familiar manipulatives, a playful learning environment, and adaptive teacher scaffolding that guided children from concrete manipulation to symbolic representation. The findings suggest that concrete manipulative play provides developmentally appropriate opportunities for constructing early mathematical understanding in kindergarten settings.